Manganese-Induced Nephrotoxicity Is Mediated through Oxidative Stress and Mitochondrial Impairment (Journal of Renal and Hepatic Disorders, 2020)
Manganese (Mn) is an essential element that is incorporated in various metabolic pathways and enzyme structures. On the other hand, a range of adverse effects has been described in association with Mn overexposure. Mn is a well-known neurotoxic agent in mammals. Renal injury is another adverse effect associated with Mn intoxication. No precise mechanism for Mn nephrotoxicity has been identified so far. The current study was designed to evaluate the potential mechanisms of Mn-induced renal injury. Rats were treated with Mn (20 and 40 mg/mL, respectively, in drinking water) for 30 consecutive days. Markers of oxidative stress, as well as several mitochondrial indices, were assessed in the kidney tissue. Renal injury was evident in Mn-treated animals, as judged by a significant increase in serum BUN and creatinine. Moreover, urinalysis revealed a significant increase in urine glucose, phosphate, and protein in Mn-treated rats. Kidney histopathological alterations, including tubular atrophy, interstitial inflammation, and necrosis, were also detected in Mn-treated animals. Biomarkers of oxidative stress, including an increment in reactive oxygen species (ROS), lipid peroxidation, and oxidized glutathione (GSSG), were detected in Mn-treated groups. On the other hand, kidney glutathione (GSH) stores and total antioxidant capacity were depleted in Mn groups. Mn exposure was associated with significant mitochondrial depolarization, decreased mitochondrial dehydrogenases activity, mitochondrial permeabilization, and depletion of adenosine triphosphate (ATP) content. These data highlight oxidative stress and mitochondrial impairment as potential mechanisms involved in Mn-induced renal injury.
Keywords: energy crisis; manganism; mitochondria; renal failure; serum electrolyte waste